Successful use of recombinant factor VII for life threatening bleeding manifestations complicating HELLP syndrome with hepatic failure - Wijeyaratne, C.N.; Samarakoon, A.B.; Dodampahala, S.H.; Jayasinghe, S.; Tudawe, M.; Seneviratne, H.R. (The Sri Lanka College of Obstetricians and Gynaecologists, 2006)
Abstract BACKGROUND: HELLP syndrome complicated by severe bleeding manifestations in pregnancy is life threatening OBJECTIVE: We report the management outcome of a woman transferred with HELLP syndrome, hepatic failure with spontaneous bleeding complicating severe pre-eclampsia. PATIENT AND METHODS: A 41 year old gravida 4 with three living children while on oral contraceptive pill had been admitted to the rural hospital with abdominal pain and vomiting with one generalised seizure where an unknown pregnancy complicated by severe hypertension was confirmed. She had been transferred in four hours to the regional teaching hospital, where eclampsia, HELLP and disseminated intravascular coagulation causing haematuria was diagnosed. She was transferred with an MgS04 infusion 12 hours later to Colombo due to lack of group specific blood in the province. On admission (18 hours since onset of symptoms) she was drowsy, icteric with asterixis, had spontaneous gum bleeding, haematuria and multiple ecchymoses with euvolumic oliguria. Her BP was 170/110 mmHg, heart rate 72/min, respiratory rate of 18/min, Sp02 99 percent (FI)2 60 percent) with right basal reduced air entry and crepitations. She had a 22-weeks gestation single live fetus with no ultrasound evidence of abruption. Laboratory results: elevated transaminases and bilirubin, prolongs 4 PT/INR, APTT, Bleeding and Clotting times, high normal creatinine / blood urea. Bedside ECHO was normal and chest radiograph showed right basal shadows. A consensus was reached that the diagnosis was disseminated intravascular coagulation complicating HELLP and eclampsia that required urgent safe termination of pregnancy per vagina. Platelet and fresh frozen plasma transfusions were given prior to central venous line insertion that caused a massive haematoma. Recombinant factor VII 35mg/kg (1.2g) infusion was given when the spontaneous bleeding stopped and prostaglandin catheter inserted into the cervix. Intravenous recombinant factor VII 1.2g was repeated 30 minutes before delivery. RESULTS: Delivery was uncomplicated by hemorrhage with no thrombotic events. She developed haemolysis on day 2 that required two packed cell transfusions. Her hypertension and renal function improved by 7th postpartum day and she was transferred back to the regional centre in good health. CONCLUSIONS AND RECOMMENDATIONS: Recombinant Factor VII infusions can be life saving and cost effective in severe DIC complicating HELLP syndrome but requires judicious use with multidisciplinary care.
Keywords: Recombinent Factor VII; HELLP; Hepatic Failure